Primeras páginas, Créditos, Tabla de contenidos. - Aguilar, Sergio (Universidad de Costa Rica, 2021)
Fascículo regular, Volumen 69(3) • julio-setiembre, 2021 www.biologiatropical.ucr.ac.cr San José, Costa Rica